Changing subplate circuits: Early activity dependent circuit plasticity - Mukherjee, Didhiti; Kanold, Patrick O. (Frontiers in Cellular Neuroscience, 2023)
Early neural activity in the developing sensory system comprises spontaneous bursts of patterned activity, which is fundamental for sculpting and refinement of immature cortical connections. The crude early connections that are initially refined by spontaneous activity, are further elaborated by sensory-driven activity from the periphery such that orderly and mature connections are established for the proper functioning of the cortices. Subplate neurons (SPNs) are one of the first-born mature neurons that are transiently present during early development, the period of heightened activity-dependent plasticity. SPNs are well integrated within the developing sensory cortices. Their structural and functional properties such as relative mature intrinsic membrane properties, heightened connectivity via chemical and electrical synapses, robust activation by neuromodulatory inputs—place them in an ideal position to serve as crucial elements in monitoring and regulating spontaneous endogenous network activity. Moreover, SPNs are the earliest substrates to receive early sensory-driven activity from the periphery and are involved in its modulation, amplification, and transmission before the maturation of the direct adult-like thalamocortical connectivity. Consequently, SPNs are vulnerable to sensory manipulations in the periphery. A broad range of early sensory deprivations alters SPN circuit organization and functions that might be associated with long term neurodevelopmental and psychiatric disorders. Here we provide a comprehensive overview of SPN function in activity-dependent development during early life and integrate recent findings on the impact of early sensory deprivation on SPNs that could eventually lead to neurodevelopmental disorders.